Quiet Quitting through Psychological Well-Being: Mindfulness Compensation and Work-Life Boundary in Retail - Ramadhi, Ramadhi; Sarianti, Kiki; Mulyadi, Olandari (Value : Jurnal Manajemen dan Akuntansi, 2025)
This study explores the role of mindfulness-based compensation and work-life boundary management in reducing quiet quitting through psychological well-being among retail employees in Padang, Indonesia. A total of 109 respondents from small and large retail businesses participated using a stratified random sampling technique. Data were gathered through a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that both mindfulness-based compensation and work-life boundary significantly affect psychological well-being and reduce quiet quitting. However, psychological well-being does not significantly influence quiet quitting and does not mediate the relationship between the two independent variables and quiet quitting. These results suggest that while organizational efforts may improve psychological well-being, they do not necessarily reduce employee disengagement. Retail companies should incorporate mindfulness elements into compensation policies and establish clear work-life boundaries to support employee engagement. Additionally, the findings point to the need for further research on other influential factors, such as job satisfaction and organizational culture, which may directly impact quiet quitting. Future studies are encouraged to examine alternative mediators to better understand disengagement and to develop more effective human resource strategies for the retail sector.